Implementasi Strategi Pemasaran dalam Penjualan Produk untuk Meningkatkan Penjualan UMKM Yubyruby Food&Drink di Desa Balun Ijuk - Excellen Mochtar Leo One; Adiva Alhaqoni; Elis Suganda; Bunga Lestari; Della Yofika; Ernita Agustin; Tiara Fitari (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Social media is an online platform designed to support social interaction among its users. By utilizing web-based technology, social media transforms traditional communication into a more dynamic interactive dialogue. Users not only act as recipients of information, but also as content producers, allowing them to share thoughts, experiences, and ideas in real-time. Digital marketing is the right solution for MSMEs to expand their marketing networks both domestically and internationally. However, the use of digital marketing by MSMEs is still very low